Diagnosis and Management of Fetal Autoimmune Atrioventricular Block - Hansahiranwadee W (Dove Medical Press, 2020)
Wirada Hansahiranwadee Division of Maternal Fetal Medicine, Department of Obstetrics and Gynaecology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Wirada HansahiranwadeeDivision of Maternal Fetal Medicine, Department of Obstetrics and Gynaecology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270, Rama 6 Road, Ratchathewee, Bangkok, ThailandTel +66 85 118 4313Fax +66 2 201 1413Email wirada.han@mahidol.ac.thAbstract: Autoimmune congenital atrioventricular block (CAVB) has been extensively studied in recent decades. The American Heart Association published guidelines for monitoring pregnant women with anti-Ro/Sjögren’s syndrome antigen A (SSA) or anti-La/Sjögren’s syndrome antigen B (SSB) autoantibodies, which are considered to increase the risk of CAVB. Information about the natural history of the disease in utero has contributed to the detection of fetuses with CAVB in the treatable stage. Hydroxychloroquine (HCQ) may be used to prevent CAVB. The lack of large randomized control trials is a major drawback to fully confirm the benefits of fluorinated steroids such as dexamethasone. Although, when combined with a β-sympathomimetic agent, the outcome of administering a fluorinated steroid in complete CAVB is still controversial. Novel treatments targeting the immunological process might prevent the recurrence of CAVB in pregnant women with previously affected children.Keywords: autoimmune congenital heart block, anti-Ro, anti-La, fetal heart block, cardiomyopathy